Hubungan Status Pekerjaan, Pendapatan dan Kepatuhan Tablet Tambah Darah dengan Riwayat Ibu Hamil Anemia - Salsabila, Isma; Andriani, Eka; Elvandari3, Milliyantri (Jurnal Ners, 2025)
Anemia is a global problem experienced by all countries, especially developing countries. According to Basic Health Research data in 2018, the incidence of anemia among pregnant women in 2018 was 48.9%, while in 2013 it was 37.1%, resulting in an increase of 11.8%. Researchers are interested in conducting research related to "The Relationship between Employment Status, Income, and Adherence to Blood Additive Tablets with the History of Anemic Pregnant Women" to find out the historical factors of anemic pregnant women. This type of research is quantitative with correlative analytic research using a cross sectional design. The population used was pregnant women in Mulyasari Village, Ciampel District. The sample in this study was 30 pregnant women with total sampling. The data collection technique used a questionnaire sheet for primary data collection and secondary data through the MCH book. The analysis test used chi square statistical test. The results showed there was no relationship between the mother's work status and the history of anemic pregnant women (p=0.850). Tidak ada hubungan pendapatan keluarga dengan riwayat ibu hamil anemia (p=0,506). Ada hubungan kepatuhan konsumsi tablet tambah darah (TTD) dengan riwayat ibu hamil anemia (p=0,000). . Sebagian besar responden berada dalam usia 20-35 tahuan dengan status pekerjaan ibu rumah tangga, Sebagian besar responden sudah dalam trimester III. Berdasarkan hasil dan pembahasan diatas dapat disimpulkan bahwa tidak ada hubungan signifikan antara status pekerjaan ibu dan pendapatan keluarga dengan riwayat ibu hamil anemia. Terdapat hubungan antara kepatuhan konsumsi tablet tambah darah (TTD) dengan riwayat ibu hamil anemia.